Decreased anthocyanidin reductase expression strongly decreases silver birch (Betula pendula) growth and alters accumulation of phenolics. Issue 4 (23rd February 2015) - Kosonen, Minna; Lännenpää, Mika; Ratilainen, Milla; Kontunen‐Soppela, Sari; Julkunen‐Tiitto, Riitta
Abstract : Phenolics, formed via a complex phenylpropanoid pathway, are important defensive agents in plants and are strongly affected by nitrogen (N) fertilization. Proanthocyanidins (PAs) are one possible endpoint of the phenylpropanoid pathway, and anthocyanidin reductase (ANR) represents a key enzyme in PA biosynthesis. In this study, the expression of silver birch ( Betula pendula ) anthocyanidin reductase BpANR was inhibited using the RNA interference (RNAi) method, in three consequent BpANR RNAi (ANRi birches) lines. The growth, the metabolites of the phenylpropanoid pathway, and the number of resin glands of the ANRi birches were studied when grown at two N levels. ANRi birches showed decreased growth and reduction in PA content, while the accumulation of total phenolics in both stems and leaves increased. Moreover, ANRi birches produced more resin glands than did wild‐type (WT) birches. The response of ANRi birches to N depletion varied compared with that of WT birches, and in particular, the concentrations of some phenolics in stems increased in WT birches and decreased in ANRi birches. Because the inhibition of PAs biosynthesis via ANR seriously affected birch growth and resulted in accumulation of the precursors, the native level of PAs in plant tissues is assumed to be the prerequisite for normal plant growth. This draws attention to the real plant developmental importance of PAs in plant tissues.